2001
DOI: 10.1097/00003246-200104000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Increased total to ionized calcium ratio during continuous venovenous hemodialysis with regional citrate anticoagulation

Abstract: Systemic citrate accumulation as evidenced by an elevated total to ionized calcium ratio occurs commonly in patients requiring CVVHD using citrate-based regional anticoagulation. Observing changes in the total to ionized calcium ratio can aid in early detection of patients with hepatic failure who are unable to appropriately metabolize citrate and will require calcium chloride infusion rates significantly above normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 13 publications
4
154
3
4
Order By: Relevance
“…Some studies have reported or applied different cut-offs of tCa/iCa ratio to define citrates overdose, e.g.2.1 [31,32], 2.25 [33], 2.4 [34], 2.5 [23,29,35,36]. Mostly the ratio of 2.1 and 2.5 are being used.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported or applied different cut-offs of tCa/iCa ratio to define citrates overdose, e.g.2.1 [31,32], 2.25 [33], 2.4 [34], 2.5 [23,29,35,36]. Mostly the ratio of 2.1 and 2.5 are being used.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate accumulation represents the most common complication of RCA, with a reported incidence of 0%-12% of patients depending on the RCA protocol used and the patient case mix (14,16,18,19,(44)(45)(46)(47)(48)(49)(50)(51). Because hepatic clearance represents the main metabolic fate of endogenous and exogenous citrate, citrate metabolism may be significantly slowed in clinical conditions where liver function is impaired, with a higher risk of citrate accumulation and consequent acid-base and electrolyte complications.…”
Section: Citrate Accumulation Risk and Rca Monitoringmentioning
confidence: 99%
“…Moreover, inadequate citrate metabolism may be associated with a fall in ionized serum calcium levels as the result of impaired calcium release from the calcium-citrate complexes. As a consequence, progressively higher calcium infusion rates may be required to maintain the ionized calcium concentration within physiologic limits, and there may be a disproportionate rise in both the total systemic calcium concentration and the total-to-ionized calcium ratio (the calcium ratio) (11,22,44,52). In clinical practice, because the calcium ratio is related to the blood citrate concentration, it is commonly accepted as an indirect index of citrate accumulation during RCA (45,48,(53)(54)(55).…”
Section: Citrate Accumulation Risk and Rca Monitoringmentioning
confidence: 99%
“…Under such conditions, the amounts of free calcium, calcium-protein complexes and the increased amount of calcium-citrate complexes add up to an increased total calcium concentration. Therefore, citrate accumulation may be detected by an increased total calcium concentration or an increased ratio of total to ionized serum calcium concentration [23]. An increased anion gap may also point towards citrate accumulation [24].…”
Section: The Downsides Of Regional Citrate Anticoagulationmentioning
confidence: 99%